Pengembangan diri pensiunan perantau Jawa melalui pelatihan Seni Gamelan di Lombok Timur - Murcahyanto, Hary; Murni, Rita Kartika; Murcahyaningrum, Salsabilla Retno Sedah Mirah (Universitas Hamzanwadi, 2023)
This study examines the positive impact of Javanese Gamelan training activities on retired Javanese migrants in East Lombok. The main focus of the research is on strengthening cultural identity, the effectiveness of training activities, contributions to education and self-development, and designing holistic social activity programs. Active participation in traditional arts, especially Javanese Gamelan, positively impacts participants' psychological well-being, strengthens their sense of cultural identity, and improves life quality in retirement. The activity not only develops cultural and artistic skills but also creates strong social networks and a sense of togetherness, reducing the risk of social isolation. This holistic approach includes active cultural arts education and skill development through Gamelan training. The research highlights the importance of understanding different cultural backgrounds and the challenges of maintaining cultural heritage and designing inclusive and supportive programs. Additionally, social activity programs are directed toward meeting participants' psychological, social, and emotional needs, creating an experience that goes beyond mere physical activity. Overall results indicate that integrating cultural arts activities with a holistic approach can have a significant positive impact on cultural identity, psychological well-being, and retirees' quality of life. Besides, social activities, particularly Gamelan training, are deemed essential for enhancing retirees' physical and mental well-being and helping them adapt to new roles post-retirement. Social and cultural activities, especially those related to traditional arts, play a crucial role in supporting retirees, preserving culture, and creating mutually supportive communities.